2020
DOI: 10.1073/pnas.1914884117
|View full text |Cite
|
Sign up to set email alerts
|

Charge-dependent interactions of monomeric and filamentous actin with lipid bilayers

Abstract: The cytoskeletal protein actin polymerizes into filaments that are essential for the mechanical stability of mammalian cells. In vitro experiments showed that direct interactions between actin filaments and lipid bilayers are possible and that the net charge of the bilayer as well as the presence of divalent ions in the buffer play an important role. In vivo, colocalization of actin filaments and divalent ions are suppressed, and cells rely on linker proteins to connect the plasma membrane to the actin network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 100 publications
(121 reference statements)
0
38
2
Order By: Relevance
“…In particular, on resting leucocytes, LFA-1 is maintained in a low activity state by an inhibitory interaction with the CAcN ( 39 , 40 ). Therefore, activation of leucocytes requires the release of CAcN-integrin interactions, so that LFA-1 can diffuse in the cell membrane and start binding activities ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, on resting leucocytes, LFA-1 is maintained in a low activity state by an inhibitory interaction with the CAcN ( 39 , 40 ). Therefore, activation of leucocytes requires the release of CAcN-integrin interactions, so that LFA-1 can diffuse in the cell membrane and start binding activities ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is encouraging, however, that this opportunity has been recognized, nucleating a rapidly growing research field ( Amaral and Pasparakis, 2019 ; Chen and Li, 2020 ). Future advancements into bioinspired and biomimetic material will likely benefit from computational approaches ( Sun et al, 2018 ; Schroer et al, 2020 ), which allow rapid advancement of theoretical and experimental data of membrane-MCA-cortex dynamics at an ever-increasing spatio-temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
“…We can still see a slightly increased intensity on the membrane, as compared to the surrounding regions, which can be attributed to the non-specific binding of actin filaments with positively charged lipids due to electrostatic forces. 71,72 Lastly, we performed a control on a planar PETA surface, where streptavidin was reconstituted with and without the formation of the lipid bilayer. As expected, we found that streptavidin was detected on the surface only with the presence of the lipids, excluding the possibility that they are simply adsorbing on the PETA surface ( Figure S7), but are selectively recruited to the membranes by biotin-streptavidin coupling.…”
Section: Lipid Patterning By Composite Printingmentioning
confidence: 99%